BIMBINGAN KELOMPOK MELALUI STRATEGI PERMAINAN UNTUK MENUMBUHKAN NILAI-NILAI KEWIRAUSAHAAN ANAK - Nafisah, Syifa Jauhar (Institut Daarul Qur'an Jakarta, Indonesia, 2020)
The study aimed to test the effectiveness of group guidance with game strategies to foster children's entrepreneurial values. This was quantitative approach with a quasi-experimental method of non equivalent pretest posttest kontrol group design. The sample of the study was 25 students in grade of IV SDN 2 Cisalak. It was taken by using nonpropability sampling technique. The instrument was a entrepreneurial values response questionnaire. The results of statistikal tests showed that group guidance with effective game strategies to grow children's entrepreneurial values is empirically demonstrated by the emergence of independent, creative, action-oriented values, courage to take risks and leadership. The study generated a new strategy for teachers in designing a curriculum that was integrated with learning to increase the entrepreneurial values of children in primary schools.